Kinerja Pegawai di Kantor Kelurahan Kabonena Kecamatan Ulujadi Kota Palu - Rian Agustian; Ahmad Sinala; Ani Susanti (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Rian Agustian, Stambuk Number B102 22 012, with the title of research on Employee Performance in the Kabonena Village Office, Ulujadi District, Palu City, supervised by Ahmad Sinala and Ani Susanti.This study aims to determine the performance of employees in the Kabonena Village Office, Ulujadi District, Palu City. This study used a method with descriptive qualitative data. The research location is located at the Kabonena Village Office. The theory used in this study is the theory proposed by Robbins, Stephen P. The informants in this study amounted to 5 (five) people. The data obtained in this study are from observations, interviews, and documentation. Data analysis methods are Data Collection, Data Condensation, Data Presentation, and Conclusion Drawing / Verification.The results of this study show that the performance of employees at the Kabonena Village Office, Ulujadi District, Palu City has not run optimally, this is due to the non-achievement of performance indicators used in this study, such as quality indicators that have not been maximized due to low responsiveness, discipline, and accuracy of employees in the agency in carrying out their duties. The quantity aspect is not maximized because there are still a number of activities that do not reach the target. Aspects of delay in completing tasks. The effectiveness aspect has not run optimally due to the resources allocated to support every activity of employees in the agency but still has not achieved the desired results in some work units. The aspect of independence has not run optimally because there are still some employees who actually transfer their duties and work to honorary employees where the work should be completed by civil servants. The aspect of work commitment has not run optimally because the work commitment of employees in the agency is still low on what is their obligation as employees.